2013
DOI: 10.1002/chem.201300903
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles under the Light: Click Functionalization by Photochemical Thiol‐yne Reaction, Towards Double Click Functionalization

Abstract: A light click away: The first application of the thiol-yne reaction to nanoparticle functionalization is described (see figure). This metal-free click chemistry approach is compatible with the addition of various molecules at the surface and can be combined with CuAAC methodology to perform chemoselective double functionalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 37 publications
0
33
0
Order By: Relevance
“…at 100°C. Concerning the spherical shape and the size distribution of the 110 obtained nanoparticles, no major differences between classical 31 P NMR (300MHz) spectra of HMBPene partial degradation. 5 conditions and microwave conditions were observed (see ESI, Fig.…”
Section: Microwave Assisted Synthesis Of Au@hmbpene Nanoparticles In mentioning
confidence: 88%
“…at 100°C. Concerning the spherical shape and the size distribution of the 110 obtained nanoparticles, no major differences between classical 31 P NMR (300MHz) spectra of HMBPene partial degradation. 5 conditions and microwave conditions were observed (see ESI, Fig.…”
Section: Microwave Assisted Synthesis Of Au@hmbpene Nanoparticles In mentioning
confidence: 88%
“…This asset facilitates nanoparticle post functionalization for biomedical as well as catalytic applications. For example, in the course of the last 8 years we developed HMBP‐coated iron oxide nanoparticles bearing carboxylate, amine and alkyne functionality and evaluate their modification through carbodiimide chemistry, copper alkyne azide cycloaddition (CuAAC) and thiol‐yne chemistry . Recently, we and others have demonstrated that HMBP could also be of great interest for the “one‐pot” synthesis and coating of gold and silver nanoparticles .…”
Section: Methodsmentioning
confidence: 99%
“…For example,i nt he course of the last 8years we developedH MBP-coated iron oxide nanoparticles bearing carboxylate, amine and alkynef unctionality and evaluate their modification through carbodiimide chemistry,c oppera lkyne azide cycloaddition (CuAAC) and thiol-yne chemistry. [25][26][27][28][29][30] Recently,w ea nd others have demonstrated that HMBP could also be of great interestf or the "one-pot" synthesis and coating of gold and silver nanoparticles. [31,32] In the case of gold nanoparticle synthesis, not only do the molecules permit the stabilization of the formed metallic nanoparticles but they also act as the reducing agent allowing their formation.T his synthesis,w hich follows am echanism related to the well-known Turkevich-Frens synthesis, produced variable sizes of relatively monodispersed nanoparticles.…”
mentioning
confidence: 99%
“…Polyethylene glycol phosphonate moieties (PO-PEG) are used as surface ligands. The phosphonate group presents high affinity for the metallic surface 113 whereas the PEG chain improves the biodistribution of the PLNPs in vivo (Figure 28D) 114.…”
Section: Chromium-doped Gallium Oxide Plnpsmentioning
confidence: 99%